Legal Regulation of Territorial Defense of Ukraine and the Place of Administrative Legislation in it - Rusetskyi, Anatolii Anatoliiovych; Lelet, Serhii Mykolaiovych; Dopilka, Vladyslav Oleksiiovych; Tsybulnyk, Nelli Yuriivna (Jurnal Cita Hukum, 2020)
AbstractThe purpose of this article is to study the specifics, and characteristics of administrative and legal regulations of the territorial defense system of Ukraine, as well as to find the optimal model of legislative changes in the field. While writing the article the following methods were used: dialectical, logical-semantic, comparative-legal, analysis and synthesis. The issues of administrative and legal regulations of territorial defense of Ukraine, as well as the peculiarities of its legislative support is considered in the article. The author's definition of the concepts “territorial defense of Ukraine” and “administrative and legal regulation” is formed and provided with the help of the analysis of scientific views. In accordance with the subject of the article, the characteristics of the practical implementation of defense policy by special public authorities, as well as the implementation of measures of administrative and legal regulations in relation to the implementation of defense measures is defined. Proposals to improve certain procedures for the introduction, and implementation of professional activities of defense policy entities and control over it are provided, as well as the importance of effective administrative and legal support of their daily lives in the course of their duties is stressed. It is proposed to amend the relevant legislation to improve the quality of effective activities of domestic defense structures, improve the system of motivational and incentive methods that can be used to defend the Ukrainian border and domestic administrative-territorial units.Keywords: Administrative and Legal Regulation, Territorial Defense and Legislative Support, State Bodies, Combat Units, International Cooperation. Abstrak:Tujuan artikel ini adalah untuk mempelajari kekhususan dan karakteristik regulasi administratif dan hukum sistem pertahanan teritorial Ukraina, serta untuk menemukan model optimal dari perubahan legislatif di lapangan. Penulisan artikel ini menggunakan metode: dialektika, logis-semantik, perbandingan-hukum, analisis dan sintesis. Masalah regulasi administratif dan hukum pertahanan teritorial Ukraina, serta kekhasan dukungan legislatifnya dipertimbangkan dalam artikel tersebut. Definisi penulis tentang konsep "pertahanan teritorial Ukraina" dan "peraturan administratif dan hukum" dibentuk dan disediakan dengan bantuan analisis pandangan ilmiah. Sesuai dengan pokok bahasan pasal tersebut, ciri-ciri pelaksanaan praktis kebijakan pertahanan oleh badan publik khusus, serta pelaksanaan tindakan-tindakan pengaturan administratif dan hukum sehubungan dengan pelaksanaan tindakan-tindakan pertahanan ditetapkan. Proposal untuk meningkatkan prosedur tertentu untuk pengenalan dan pelaksanaan kegiatan profesional entitas kebijakan pertahanan dan kontrol atasnya disediakan, serta pentingnya dukungan administratif dan hukum yang efektif dalam kehidupan sehari-hari guna menjalankan tugas mereka. Diusulkan untuk mengubah undang-undang yang relevan dalam rangka meningkatkan kualitas kegiatan yang efektif dari struktur pertahanan dalam negeri, meningkatkan sistem metode motivasi dan insentif yang dapat digunakan untuk mempertahankan perbatasan Ukraina dan unit administrasi-teritorial domestik.Kata Kunci: Pengaturan Administrasi dan Hukum, Pertahanan Teritorial, Dukungan Legislatif, Badan Negara, Satuan Tempur, Kerjasama Internasional. АннотацияЦелью данной статьи является: 1) изучение специфики и характерных особенностей административно-правового регулирования системы территориальной обороны Украины; 2) поиск оптимальной модели законодательных изменений в этой сфере государственной деятельности. При написании статьи автора использовали такие методы, как: диалектический, логико-семантический, сравнительно-правовой, анализа и синтеза. Рассмотрены вопросы административно-правового регулирования территориальной обороны Украины, а также особенности законодательного обеспечения данной сферы государственной деятельности. С помощью анализа научных взглядов сформулировано авторское видение понятия «территориальная оборона Украины» и «административно-правовое регулирование». В соответствии с тематикой исследования: а) выделены характерные особенности практического осуществления оборонной политики специальных органов государственной власти; б) определены возможные направления реализация мер административно-правового регулирования оборонных мероприятий. Сформулированы предложения по совершенствованию отдельных процедур осуществления профессиональной деятельности субъектов проведения оборонной политики и контроля за ней. Отмечена важность эффективного административно-правового обеспечения повседневной жизнедеятельности таких субъектов, и особенно при реализации предоставленных полномочий. Предложено внесение изменений в профильное законодательство с целью повышения качественного уровня эффективной деятельности отечественных оборонных структур, совершенствования системы мотивировочных и поощрительных методов, которые могут применяться в целях обороны украинских границ и административно-территориальных единиц.Ключевые слова: Административно-правовое регулирование, Территориальная оборона, Законодательное обеспечение, Государственные органы, Боевые подразделения, Международное сотрудничество.